Immunometabolic adaptation and immune plasticity in pregnancy and the bi-directional effects of obesity - April Rees (Clinical and Experimental Immunology, 2022)
Mandatory maternal metabolic and immunological changes are essential to pregnancy success. Parallel changes in metabolism and immune function make immunometabolism an attractive mechanism to enable dynamic immune adaptation during pregnancy. Immunometabolism is a burgeoning field with the underlying principle being that cellular metabolism underpins immune cell function. With whole body changes to the metabolism of carbohydrates, protein and lipids well recognised to occur in pregnancy and our growing understanding of immunometabolism as a determinant of immunoinflammatory effector responses, it would seem reasonable to expect immune plasticity during pregnancy to be linked to changes in the availability and handling of multiple nutrient energy sources by immune cells. While studies of immunometabolism in pregnancy are only just beginning, the recognised bi-directional interaction between metabolism and immune function in the metabolic disorder obesity might provide some of the earliest insights into the role of immunometabolism in immune plasticity in pregnancy. Characterised by chronic low-grade inflammation including in pregnant women, obesity is associated with numerous adverse outcomes during pregnancy and beyond for both mother and child. Concurrent changes in metabolism and immunoinflammation are consistently described but any causative link is not well established. Here we provide an overview of the metabolic and immunological changes that occur in pregnancy and how these might contribute to healthy versus adverse pregnancy outcomes with special consideration of possible interactions with obesity.